Innovations and Challenges in the Preservation of the Batak Language by the Protestant Batak Christian Huria Church (HKBP) among Youth in the Context of Urbanization in Jakarta - Hotmauli Sihombing, Tetty (Sahabat Publikasi, 2024)
In the dynamic urban context of Jakarta, the preservation of regional languages faces significant challenges, especially among the younger generation. This study examines the role of the Huria Christian Batak Protestant Church (HKBP, a Protestant Batak Christian Church) in maintaining the existence of the Batak language in the midst of urbanization, by applying social identity theory to understand the dynamics of language preservation and cultural identity. Using a qualitative approach, the study involved in-depth interviews with 30 young congregations and 10 key HKBP figures, as well as participatory observation of church activities over a six-month period. The results of the analysis revealed that HKBP's main efforts in preserving the Batak language are centered on the use of the language in worship, with 75% of respondents stating the importance of this practice. The study also identified several additional initiatives, such as cultural seminars, cultural performances, and the use of traditional musical instruments in worship. The main challenges faced include the low enthusiasm of the younger generation (60% of respondents), the pressure of assimilation of metropolitan culture, and the limitations of effective preservation programs outside the context of worship. The findings emphasized the importance of developing more comprehensive and innovative strategies, including the potential use of digital technology and social media, to increase the appeal of the Batak language among urban youth. This research results in a religious community-based language preservation model that can be applied in urban contexts, offering a new perspective in urban sociolinguistic studies and cultural diversity management. The strategic recommendations are prepared to maximize the role of religious institutions as agents of cultural preservation, with a focus on synergy between churches, families, and urban Batak communities. This study highlights the potential and challenges of religious institutions in bridging tradition and modernity, as well as maintaining cultural identity amid urban social complexity. Although limited to the context of HKBP in Jakarta, these findings provide valuable insights for the study of minority language preservation in urban environments more broadly